2010
DOI: 10.1007/s00580-010-1077-3
|View full text |Cite
|
Sign up to set email alerts
|

Associations between serum amylase, lipase and pancreatic specific lipase in dogs

Abstract: Acute pancreatitis is a common and potentially life-threatening disease in dogs. Diagnosis of pancreatitis relies on a combination of history, clinical evaluation, serum biochemistry analysis, imaging, pancreatic specific lipase and in some cases, biopsy and histology. Amylase and lipase have traditionally been utilised as cheap and non-invasive indicators of pancreatic disease; however, these analytes have limited sensitivity and specificity. Newer tests such as pancreatic specific lipase offer higher sensiti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 11 publications
0
3
0
Order By: Relevance
“…This finding is not unexpected because pancreatic lipase is negatively charged and fairly large, with a molecular mass of approximately 50.7 kDa 81 . A retrospective study of 864 serum samples at a commercial laboratory found that azotemic dogs had higher median amylase activity, lipase activity, and cPLI concentrations when compared to nonazotemic dogs 82 . Likewise, a retrospective study documented that renal disease was the most common nonpancreatic cause of increased DGGR lipase activity, but the increases were poorly correlated with plasma creatinine concentrations, suggesting a complex interaction 83 .…”
Section: Pancreatic Lipase Concentrations In Dogs With Primary Diseases Other Than Pancreatitismentioning
confidence: 92%
See 1 more Smart Citation
“…This finding is not unexpected because pancreatic lipase is negatively charged and fairly large, with a molecular mass of approximately 50.7 kDa 81 . A retrospective study of 864 serum samples at a commercial laboratory found that azotemic dogs had higher median amylase activity, lipase activity, and cPLI concentrations when compared to nonazotemic dogs 82 . Likewise, a retrospective study documented that renal disease was the most common nonpancreatic cause of increased DGGR lipase activity, but the increases were poorly correlated with plasma creatinine concentrations, suggesting a complex interaction 83 .…”
Section: Pancreatic Lipase Concentrations In Dogs With Primary Diseases Other Than Pancreatitismentioning
confidence: 92%
“… 81 A retrospective study of 864 serum samples at a commercial laboratory found that azotemic dogs had higher median amylase activity, lipase activity, and cPLI concentrations when compared to nonazotemic dogs. 82 Likewise, a retrospective study documented that renal disease was the most common nonpancreatic cause of increased DGGR lipase activity, but the increases were poorly correlated with plasma creatinine concentrations, suggesting a complex interaction. 83 An additional study noted a high prevalence of increased Spec cPL (Texas A&M University, Gastrointestinal Laboratory) concentrations in dogs with hemodialysis‐dependent AKI.…”
Section: Pancreatic Lipase Concentrations In Dogs With Primary Diseases Other Than Pancreatitismentioning
confidence: 99%
“…The most common biomarkers for AP currently used in dogs are lipase activity using the 1,2‐ o ‐dilauryl‐rac‐glycero glutaric acid‐(6′‐methylresorufin) ester assay (DGGR‐lipase) and concentrations of canine pancreas‐specific lipase (cPL; Spec cPL, IDEXX laboratories), 6‐8 both of which may be affected by extrapancreatic diseases 9‐12 . In particular, increased cPL concentrations or lipase activity have been reported in dogs with kidney disease, 13‐15 with cPL concentrations ≥400 μg/L in 21/30 dogs with severe AKI in 1 study 14 . However, most studies showed poor correlation between plasma creatinine concentrations and either lipase activity or cPL concentrations 16‐18 …”
Section: Introductionmentioning
confidence: 99%